(untitled) (Филология, 2026)
Radoslava Minkova, Diana Stantcheva, Ewa Wojno-Owczarska, Alexandra Preitschopf, Stanislava Ilieva (Hrsg.): Wendezeiten. Erfahrungen – Erwartungen – Erzählungen. Пловдив: Университетско издателство „Паисий Хилендарски“, 2023, 353 с. ISBN 978-619-202-826-8 (print); ISBN 978-619-202-827-5 (online).